SPECIFIC FEATURES OF THE DEVELOPMENT OF THE REGIONS OF THE REPUBLIC OF UZBEKISTAN - Salayeva Guli Mansurovna (Antis Publisher, 2026)
Objective: This article analyses the specific features of the economic development of the regions of the Republic of Uzbekistan, focusing on interregional disparities, growth factors, and cluster dynamics. The background of the study stems from the global trend toward industrial clusters and spatial economic transformation. The research aims to evaluate the current economic performance, industrial concentration, and regional disparities across the administrative territories of Uzbekistan. Method: Methodologically, the study utilizes a complex approach integrating A. Weber’s industrial location theory, F. Perroux’s growth poles concept, and new economic geography models, alongside clustering, dynamic comparison, and analytical methods applied to regional statistical data (GRP, per capita indicators, and investment flows). Results: The key findings reveal that regional growth is unevenly distributed, with resource-based regions and metropolitan areas like Navoi and Tashkent City exhibiting the highest GDP per capita and investment inflows, whereas agrarian-reliant regions demonstrate slower industrial expansion. Novelty: The conclusions emphasize that while overall macroeconomic growth remains positive, future policy interventions must target balanced regional development, infrastructure enhancement, and the active deployment of cluster mechanisms to reduce disparities.